(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
This study discusses the phenomenon of intertextuality in the poetry of Khalil Mardam Bik within an applied study of religious intertextuality; as one of the diverse cultural repertories that have settled in the memory of the poet during long periods of time. The poet has dealt with it through the intersection or interaction with his texts and images to generate new semantics of meanings and images including expanding the perception of the recipient and his interaction with the poet’s intellectual and human visions. This study is based on the treatment of this artistic phenomenon in the poetry of Khalil Mardam Bik as an independent phenomenon that has not been analyzed and studied before. The researcher examines it with a descriptive analytical approach by revealing the poet’s relationship with religious heritage، and how his texts were overlapped with Qur’an through its meanings or words or stories and characters. The research also reveals how the poet was inspired by the contents of the Hadith and its rich connotations of wisdom and good advice